(untitled) (Plant Tissue Culture and Biotechnology, 2017)
Salinity stress is one of the major adversarial impacts of climate change that limits crop productivity worldwide, especially in developing countries. To overcome this situation it is necessary to understand the cellular basis of salt stress tolerance mechanisms. Various genes involved in ion exclusion, osmotic tolerance, Reactive Oxygen Species (ROS) scavenging and other regulation mechanisms influence salinity tolerance in crops. Function of these candidate genes/sequences may vary in different plants and within different tissues. For the last two decades, in Bangladesh several approaches have been taken to develop transgenic rice, the staple crop. Work is in progress to monitor stable incorporation of these transgenes. Further evaluation is needed to check their adaptation/resistance in natural environments. Good performance in field conditions will lead to acceptance of these varieties for commercial productions in order to ensure food security. Plant Tissue Cult. & Biotech. 27(2): 241-256, 2017 (December)